Pengaruh Lebel Syariah terhadap Keputusan Konsumen dalam Pendekatan Neuromarketing dengan Teknik Eye Tracking dan Facial Coding - Istingadah, Istingadah (Program Studi Perbankan Syariah STAI Senori Tuban, 2025)
This study aims to analyze the influence of the sharia label on consumer decision-making using a neuromarketing approach through eye tracking and facial coding techniques. The research is motivated by the limited visual attention consumers give to Sharia labels in Islamic banking promotions, as well as increasing consumer skepticism regarding the authenticity of such labels. This study employs a theoretical qualitative method based on an in-depth literature review of eye tracking, facial coding, and Muslim consumer psychology. Findings indicate that sharia labels that are minimally designed and placed in non-strategic visual areas fail in capturing initial visual attention. Furthermore, theoretical facial coding analysis suggests that positive emotional responses only emerge when the label is perceived as an authentic representation of Islamic values. Conversely, when the label is viewed merely as a marketing strategy without substance, negative emotional expressions are more likely to occur. Thus, the effectiveness of sharia labels is highly dependent on both the strength of visual design and the perceived authenticity of values factors that operate at a subconscious level and significantly influence consumer decisions level and significantly influence consumer decisions.